Semantic caching in large scale querying systems - d'Orazio, Laurent; Roncancio, Claudia; Labbé, Cyril; Jouanot, Fabrice (Revista Colombiana de Computación, 2008)
Caching is crucial to improve performances in many computing system. This work proposes a caching approach for improving query evaluatión. Keywords: semantic, cooperatión, grid, data querying.